Stability analysis of DPC in the FSRF for grid‐connected converter. Issue 5 (18th February 2020) - Chen, Liang; Nian, Heng; Xu, Yunyang
Abstract : The fixed‐frequency synchronous reference frame‐based direct power control (FSRF‐DPC) strategy is investigated in this study, which can avoid the phase‐locked loop. However, the existing research are focused on its application in a strong grid, where grid impedance is assumed as zero. The effect of grid impedance on FSRF‐DPC strategy is ignored, and the stability of FSRF‐DPC controlled converter in a weak grid is not clear. To fill this gap, the impedance‐based stability analysis is adopted. The sequence domain impedance of FSRF‐DPC controlled grid‐connected converter is developed in this study. The equivalent decoupled sequence domain impedance of FSRF‐DPC controlled converter is further extracted by loop decomposition technique. The impacts of controller parameters and grid impedance on the equivalent sequence domain impedance are studied. A damping method by modifying the voltage feedforward term is investigated based on the stability requirement on the impedance characteristic. Finally, simulations and experiments are carried out to verify the correctness of the proposed impedance model of FSRF‐DPC controlled converter as well as the effectiveness of the proposed damping method.